Fetal cardiovascular function in a late-onset SGA and FGR cohort: CURIOSA study - Lobmaier, Silvia M.; Graupner, Oliver; Franke, Christina; Boess, Nadia; Haller, Bernhard; Oberhoffer, Renate; Wacker-Gussmann, Annette; Ortiz, Javier U. (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
The measurement of fetal cardiovascular function parameters is not yet established in prenatal diagnostics. Now that the research field of fetal programming is becoming increasingly important, this might change. Fetal cardiovascular changes have been described above all in early/severe fetal growth restriction (FGR). The aim of this study was to investigate functional echocardiographic parameters in fetuses with late-onset small for gestational age (SGA)/FGR.A prospective cohort of SGA fetuses (including FGR) and a control group with similar distribution of gestational age were studied. Parameters of systolic, diastolic, and global cardiac function, morphometry and measurements of the fetal abdominal aorta were collected.A total of 149 SGA fetuses and 143 control fetuses were included from 32 weeks until term. The total SGA group was further divided into SGA 3rd–10th (fetuses between the 3rd and 10th weight percentile) and FGR subgroups. In the total SGA group, relative right and left ventricular wall thickness, left E/A ratio, isovolumetric contraction time and left myocardial performance index were significantly increased compared to controls after adjustment for gestational age. MAPSE, TAPSE, ejection time, left cardiac output, and abdominal aortic distensibility were significantly lower. The changes were more pronounced in the FGR subgroup.Even in a group of late-onset SGA/FGR, echocardiographic parameters are already altered in utero.
Keywords: fetal cardiac function; small for gestational age; fetal growth restriction; SGA; FGR